(untitled) (GEON Journal (Management, Organizations and Business), 2018)
The general objective of this research was to determine the fulfillment of the qualification criteria of the Homologation Levels that the SME providers of SiderPerú-Gerdau, Chimbote, 2016 should have. The design of the study was non-experimental-transversal. A sample population of 45 companies was used and a questionnaire was applied, obtaining the following results: of the 45 companies that entered the first level, 100% met all the qualification criteria. Of the 45 companies that entered the Second Level, 58% met the qualification criteria. Of the total number of companies that entered the Third Level, 92% met the qualification criteria. Concluding that, if all the qualification criteria of homologation are met, the companies are expedited to be considered suppliers of Sider Peru.